1992
DOI: 10.1523/jneurosci.12-04-01511.1992
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ventromedial medulla "multimodal, multireceptive" neurons in opiate spinal descending control system: a single-unit study of the effect of morphine in the awake, freely moving rat

Abstract: In the present work, we have studied the effects of systemic morphine on the electrophysiological properties of ventromedial medulla (VMM) neurons in the awake, freely moving rat. By means of a chronically implanted single-unit recording device, a drug delivery catheter, and the use of controlled innocuous and noxious cutaneous stimuli, we were able to study precisely the spontaneous and evoked VMM neuronal activities. We have particularly focused our attention upon the VMM "multimodal, multireceptive" units, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
5
17
0
Order By: Relevance
“…Since suppression of the phasic responses of RM cells to noxious stimulation accompanies withdrawal suppression, it is the suppression of phasic cellular responses that mediates RM antinociception. Our findings confirm results obtained from ON cells in awake rats and reported 20 years ago, and extend our understanding to include the responses of OFF cells to morphine in an unanesthetized preparation (Martin et al, 1992). Moreover, we propose a unified model that connects the activity recorded from RM cells in unanesthetized and anesthetized rodents alike to nociceptive reactions.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Since suppression of the phasic responses of RM cells to noxious stimulation accompanies withdrawal suppression, it is the suppression of phasic cellular responses that mediates RM antinociception. Our findings confirm results obtained from ON cells in awake rats and reported 20 years ago, and extend our understanding to include the responses of OFF cells to morphine in an unanesthetized preparation (Martin et al, 1992). Moreover, we propose a unified model that connects the activity recorded from RM cells in unanesthetized and anesthetized rodents alike to nociceptive reactions.…”
Section: Discussionsupporting
confidence: 90%
“…Tonic excitation of OFF cells and inhibition of ON cells in response to various opioids administered by different routes techniques are consistent, often replicated, findings in anesthetized rats (Toda, 1982;Heinricher and Rosenfeld, 1985;Barbaro et al, 1986;Fang et al, 1989;Heinricher et al, 1992Heinricher et al, , 1994Brink et al, 2006;Hellman et al, 2007). However, a single study in the unanesthetized rat did not observe any change in tonic ON cell activity in response to morphine as is observed in anesthetized rats (Martin et al, 1992). This singular study reported that in response to morphine, the tonic activity of ON-like cells did not change.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Off cells increase their firing rate just prior to nociceptive withdrawal reflexes and become continuously active following systemic or supraspinal opioid administration. Although some investigators have not observed off cells in awake rats (Oliveras et al, 1990;Martin et al, 1992) recently McGaraughty et al (1993) have demonstrated characteristic off-cell responses to systemic morphine in awake rats. On cells exhibit responses opposite to those of off cells; they increase their firing rate in response to noxious stimuli and are inhibited by morphine administration.…”
mentioning
confidence: 99%